Kinking of an open stent graft after total arch replacement with the frozen elephant technique for acute Type A aortic dissection. (10th January 2018) - Morisaki, Akimasa; Isomura, Tadashi; Fukada, Yasuhisa; Yoshida, Minoru
Abstract: Recently, in Japan, the J Graft Open Stent Graft (JOSG) was commercialized for surgical repair of an aortic aneurysm and aortic dissection and the frozen elephant trunk technique was applied. Kinking of the JOSG is a rare adverse event that requires additional intervention. We experienced 2 patients who developed kinking of a JOSG after translocated total arch replacement with the frozen elephant trunk technique for acute Type A aortic dissection. Both patients had intermittent claudication with a decreased ankle–brachial pressure index after the operation. Computed tomography angiography showed kinking between the non-stent and stent parts of the JOSG. Therefore, we performed endovascular repair. A severely angulated arch preserved by a translocated technique may lead to kinking of a JOSG. This suggests that the removed non-stent part should be as short as possible to prevent kinking of the JOSG.